Kontribusi Gaya Kepemimpinan Kepala Sekolah, Motivasi Kerja, Iklim Kerja dan Etos Kerja Terhadap Kinerja Guru di SMA Negeri 2 Tejakula - K.Y. Artawan; A.A.G. Agung; I.G.K.A. Sunu (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aims to determine the magnitude of the relationship between principal transformational leadership style variables, communication style, work ethic, and work motivation on teacher performance at SMK Negeri 2 Tejakula. This type of research is ex post facto with multiple linear regression analysis designs. The population in this study was 50 people. The research sample of this research was 44 people. Collecting data using a questionnaire about the principal's transformational leadership style, communication style, work ethic, and work motivation on teacher performance. The collected data were analyzed using correlation analysis techniques, multiple regression, and partial correlation. The results showed that (1) there is a relationship between the principal's transformational leadership style and teacher performance at 57.7%, (2) there is a relationship between communication style and teacher performance at 71.0%, (3) there is a relationship between work ethic and teacher performance by 75.5%, (4) there is a relationship between work motivation and teacher performance by 49.7%, and (5) there is a relationship between the school principal's transformational leadership style, communication style, work ethic and work motivation which are significantly correlated with performance teachers with a correlation of 85.2%.